"Utopianism in Pianissimo": Adorno and Bloch on Utopia and Critique. Issue 3 (3rd July 2022) - Roessler, Jonathan
ABSTRACT: Adorno's subtle utopianism is often overshadowed by the sombreness of his work. In this article, I explore Adorno's concept of utopia by reading him alongside Ernst Bloch, whose The Spirit of Utopia (1918) had a lasting influence on Adorno. Not least due to the unsteady nature of their friendship, the intellectual relationship between Bloch and Adorno has often been overlooked. I propose that Bloch's utopianism can help us make sense of Adorno's rare but distinct remarks on utopia and argue that instead of being a pure negativist, Adorno entertains a "minimal utopianism" that is constitutive to his notion of critique. I conclude that reading Adorno with Bloch reveals utopia as an ineliminable focal point in Adorno's work and urges us to rethink the importance of utopianism for any critical project.